Communication Sciences and Disorders PhD Graduates' Perceptions of Their PhD Program. - Crais, Elizabeth; Harrison Savage, Melody (Perspectives of the ASHA Special Interest Groups, 2020)
Purpose: The shortage of doctor of philosophy (PhD)--level applicants to fill academic and research positions in communication sciences and disorders (CSD) programs calls for a detailed examination of current CSD PhD educational practices and the generation of creative solutions. The intended purposes of the article are to encourage CSD faculty to examine their own PhD program practices and consider the perspectives of recent CSD PhD graduates in determining the need for possible modifications. Method: The article describes the results of a survey of 240 CSD PhD graduates and their perceptions of the challenges and facilitators to completing a PhD degree; the quality of their preparation in research, teaching, and job readiness; and ways to improve PhD education. Results: Two primary themes emerged from the data highlighting the need for "matchmaking." The first time point of needed matchmaking is prior to entry among students, mentors, and expectations as well as between aspects of the program that can lead to students' success and graduation. The second important matchmaking need is between the actual PhD preparation and the realities of the graduates' career expectations, and those placed on graduates by their employers. Conclusions: Within both themes, graduate's perspectives and suggestions to help guide future doctoral preparation are highlighted. The graduates' recommendations could be used by CSD PhD program faculty to enhance the quality of their program and the likelihood of student success and completion. Supplemental Material: https://doi.org/10.23641/asha. 11991480